Effect of Cellular Mobile Phone Use and Cetrizine on Hand-Eye Coordination and Visual Acuity - Gawit, Kalpita Ganpat (J Clin Diagn Res, 2017)
INTRODUCTION: Cellular mobile phones are a major cause of distraction especially while driving. The aggressive and inappropriate use of cellular mobile phones has increased the risk of accidents. Similar alerts are available in literature for certain substances and drugs (e.g. second generation anti H1 drug –Cetirizine) which also derange psychomotor performance and parameters of alertness. AIM: This study measured variations in hand-eye coordination and visual acuity due to use of cellular mobile phone in comparison to that of commonly used antihistaminic drug viz., single dose Cetirizine 10 mg. MATERIALS AND METHODS: It was a single blind, single dose, interventional study, 100 healthy human volunteers divided into two groups. Baseline readings of all volunteers were noted. Group-I (n=50) was Cetirizine group (10mg orally stat), Group –II (n=50) Cellular mobile phone user group. Alertness was tested on hand– steadiness tester (Reaction Time Index = RTI) and on Flicker–fusion apparatus (visual acuity - Critical Flicker Fusion Frequency per second= CFFF/sec). Baseline readings of all volunteers were noted before intervention. Baseline was compared with readings at three hour post-intervention and was analysed by paired t-test. Inter-group comparison of parameters was also done and was analysed by unpaired t-test. RESULTS: The baseline RTI (95.46±41.74, 85.11±39.05) and CFF low and high (40.07±9.970, 40.76±9.309 and 40.42±9.035, 40.48±9.863) respectively, in Cetirizine group and Mobile user group were comparable. The RTI increased significantly (116.4±51.46, 102.8±49.26) in both the groups after intervention. However, there is no significant change in CFF intensity from baseline in either group post-intervention. CONCLUSION: Concurrent use of mobile phone while performing tasks, showed significant impairment of hand–steadiness which was comparable to that produced by single dose Cetirizine 10 mg and this may be one of the factors contributing to their close association with road traffic accidents.